2022
DOI: 10.1016/j.autneu.2021.102918
|View full text |Cite
|
Sign up to set email alerts
|

Central sympathetic network for thermoregulatory responses to psychological stress

Abstract: In mammals, many types of psychological stressors elicit a variety of sympathoexcitatory responses paralleling the classic fight-or-flight response to a threat to survival, including increased body temperature via brown adipose tissue thermogenesis and cutaneous vasoconstriction, and increased skeletal muscle blood flow via tachycardia and visceral vasoconstriction. Although these responses are usually supportive for stress coping, aberrant sympathetic responses to stress can lead to clinical issues in psychos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 116 publications
0
24
0
Order By: Relevance
“…Increases in body temperature from 38 to 41°C in rats have been shown to increase sympathetic nerve discharge rate ( 11 , 25 ), and may be supporting the hyper-catecholaminergic state present in the rat when isoproterenol is administered, particularly given the half-life of isoprenaline is <5 minu and a single dose of isoprenaline has been shown to induce persistent pathological cardiac changes ( 12 ). AMP-activated protein kinase (AMPK) is ubiquitously expressed throughout the body, and has been implicated in the pathophysiology of TTS as endomyocardial tissue biopsies taken during the acute TTS phase show increased PI3K/Akt pathway activity ( 26 ), which can be activated by AMPK ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increases in body temperature from 38 to 41°C in rats have been shown to increase sympathetic nerve discharge rate ( 11 , 25 ), and may be supporting the hyper-catecholaminergic state present in the rat when isoproterenol is administered, particularly given the half-life of isoprenaline is <5 minu and a single dose of isoprenaline has been shown to induce persistent pathological cardiac changes ( 12 ). AMP-activated protein kinase (AMPK) is ubiquitously expressed throughout the body, and has been implicated in the pathophysiology of TTS as endomyocardial tissue biopsies taken during the acute TTS phase show increased PI3K/Akt pathway activity ( 26 ), which can be activated by AMPK ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was noticed during initial experiments that body temperature tended to rise after isoprenaline administration. A rise in body temperature is known to be produced by high catecholamine levels (once known as “emotional fever”) ( 11 ), as is a suite of immunoinflammatory changes ( 12 ). In our experiments, the rise in body temperature was controlled by adjusting the external heating support for the anesthetized animal, which remained euthermic throughout.…”
Section: Introductionmentioning
confidence: 99%
“…The DP and TTd are located in the medial part of the olfactory peduncle. They project to the dorsomedial hypothalamus (DMH) that targets to sympathetic premotor neurons in the brainstem ( Figure 1 ; Nakamura and Morrison, 2022 ). This observation suggests that the DP and TTd transform the retronasal odor information to sympathetic stress-responses.…”
Section: Two Processing Streams Of Olfactory Informationmentioning
confidence: 99%
“…Then, which neural pathway is responsible for the stress responses to retronasal odors? It has been shown that the DP and TTd in the medial OC play a role as a hub in transforming a variety of psychological stress-signals to sympathetic thermogenesis and cardiovascular responses via the pathway through DMH, rostral medullary raphe region (rMR), and rostral ventrolateral medulla (RVLM) ( Figure 1 ; Kataoka et al, 2020 ; Nakamura and Morrison, 2022 ). Because the DP and TTd receive rich inputs from MCs and TCs in the medial map of the OB, we speculate that stress-inducing internal odors activate the DP and TTd and transmit aversive odor signals to the DMH-rMR/RVLM-sympathetic pathway, thus inducing the sympathetic responses.…”
Section: External and Internal Odors Inducing Stress Responsesmentioning
confidence: 99%
See 1 more Smart Citation